Quarter Life Crisis Among Fresh Graduates: Causes, Impacts, and Coping Strategies - Muhammad Ihsan Prahasta; Syahrul Hidayat Putra Baso (Proceedings of the 1st International Conference on Social Science (ICSS), 2025)
The prevalence of the phenomenon of quarter life crisis (QLC) among fresh graduates has become increasingly evident in the context of contemporary social and economic challenges. QLC is characterized by a state of confusion, anxiety, and uncertainty regarding the transition to adulthood. This psychological distress is further exacerbated by the prevailing economic instability and high unemployment rates in Indonesia. The objective of this study is to identify the causes, impacts, and coping strategies of QLC among fresh graduates. The study will be guided by a Systematic Literature Review (SLR) method that adheres to the PRISMA guidelines. The findings indicated that social support, social media use, and economic conditions exerted a substantial influence on the QLC experience. The emotional distress experienced by the subjects was mitigated, to some extent, by the support provided by family and friends. Conversely, excessive social media use had a deleterious effect on the subjects' stress levels and self-confidence issues. The repercussions of the QLC encompassed elevated levels of emotional distress, familial discord, and uncertainty in discerning a vocational trajectory. This study underscores the necessity for suitable interventions to assist young adults in coping with the challenges posed by QLC and cultivating effective adaptation strategies.